Destination NATO : defence reform in Bosnia and Herzegovina, 2003-13 - Maxwell, Rohan; Olsen, John Andreas, 1968-; Royal United Services Institute for Defence and Security Studies (Abingdon [England] : Routledge Journals, 2013)
Defense reform has been a major component of Bosnia's stabilization and nation-building. Though true for many cases of post-conflict transition, it is especially so for Bosnia, which arguably has the most complex state structure in Europe. Ten years on from the start of Bosnia's defense-reform process, Destination NATO records and reviews the Bosnian experience of defense reform. The monograph offers policy-makers, practitioners and academics knowledge of the specific case of Bosnia and Herzegovina, and makes these insights relevant to defense-reform efforts in other contexts.
Introduction :'mission BiH' -- War and peace -- Consensus and agreement -- Implementation and challenges -- Lessons from defence reform in BiH -- Conclusion : destination NATO.
Includes bibliographical references.
Keywords: North Atlantic Treaty Organization; Bosnia and Herzegovina -- Defenses